High Utility Text and Data Mining Methods - Kanimozhi, R (International Journal of Computer Sciences and Engineering, 2025)
Text data has continuous growth of volumes of data, automate extract ion of implicit, previously unknown, and potentially useful information becomes more necessary to properly utilize this vast source of knowledge. Text mining corresponds to the extension of the data mining approach to textual data and is concerned with various tasks, such as extraction of information implicitly contained in collection of documents, or similarity-based structuring. This paper provides the reader with a very brief introduction to some of the theory and methods of text data mining. The intent of this paper is to introduce some of the current text mining methods that are employed within this discipline area. In this paper we provide some of methods of text datamining